Alterations of ecosystem nitrogen status following agricultural land abandonment in the Karst Critical Zone Observatory (KCZO), Southwest China - Liu, Man; Han, Guilin (PeerJ, 2023)
Background Secondary succession after agricultural land abandonment generally affects nitrogen (N) cycle processes and ecosystem N status. However, changes in soil N availability and NO3– loss potential following secondary succession are not well understood in karst ecosystems. Methods In the Karst Critical Zone Observatory (KCZO) of Southwest China, croplands, shrub-grass lands, and secondary forest lands were selected to represent the three stages of secondary succession after agricultural land abandonment by using a space-for-time substitution approach. The contents and 15N natural abundance (δ15N) of leaves, soils, and different-sized aggregates at the three stages of secondary succession were analyzed. The δ15N compositions of soil organic nitrogen (SON) in aggregates and soil to plant 15N enrichment factor (EF = δ15Nleaf −δ15Nsoil), combined with soil inorganic N contents and δ15N compositions were used to indicate the alterations of soil N availability and NO3–loss potential following secondary succession. Results Leaf N content and SON content significantly increased following secondary succession, indicating N accumulation in the soil and plant. The δ15N values of SON also significantly decreased, mainly affected by plant δ15N composition and N mineralization. SON content in macro-aggregates and soil NH4+ content significantly increased while δ15N values of NH4+ decreased, implying increases in SON stabilization and improved soil N availability following secondary succession. Leaf δ15N values, the EF values, and the (NO3–-N)/(NH4+-N) ratio gradually decreased, indicating reduced NO3– loss following secondary succession. Conclusions Soil N availability improves and NO3– leaching loss reduces following secondary succession after agricultural land abandonment in the KCZO.
Keywords: Soil N availability; NO3– loss potential; 15N natural abundance; Soil aggregates; Secondary succession; Karst critical zone observatory